Pyla-Koutsopetria Archaeological Project: Excavations at Pyla-Vigla in 2019 - Stephens, Justin; Olson, Brandon R.; Landvatter, Thomas; Moore, R. Scott (Journal of Hellenistic Pottery and Material Culture, 2019)
The site of Vigla, excavated under the auspices of the Pyla-Koutsopetria Archaeological Project (PKAP), is a fortified settlement located east of modern Larnaca on the island of Cyprus (fig. 1). Primarily dating to the early Hellenistic period, Vigla offers the possibility of illuminating the island’s role in the early Hellenistic period, when Cyprus came under the control of Alexander the Great and a selection of his successors. Scholarly focus on the early Hellenistic period on Cyprus has been limited compared to previous eras, in particular the Bronze Age and Classical period, when Cyprus and its city-kingdoms were largely able to exercise a certain level of independence. The significance of Vigla lies in its ability to shed light on the very difficult logistical and chronological issues that surround the early Hellenistic occupation of Cyprus. In general, the chronology of the early Hellenistic period is problematic, as both material and literary sources are limited for the crucial decades following the tumultuous events surrounding Alexander’s death and the conflicts of his successors. Vigla has the potential to provide much needed material evidence to help parse the chronological problems of the early Hellenistic period, and it represents an opportunity to examine mechanisms of subjugation and control used by Alexander’s successors in conquering Cyprus.